Deleuze, a philosophy of the event : together with the vocabulary of Deleuze - Zourabichvili, Francois; Lambert, Gregg, 1961-; Smith, Daniel W. (Daniel Warren), 1958-; Aarons, Kieran; Zourabichvili, Fran's. (Edinburgh : Edinburgh University Press, 2012)
'This edition makes a new translation of two of Zourabichvili's most important writings on the philosophy of Gilles Deleuze available in a single volume. Deleuze: A Philosophy of the Event (1994) is an exposition of Deleuze's philosophy as a whole, while the complementary Deleuze's Vocabulary (2003) approaches Deleuze's work through an analysis of key concepts in a dictionary form. From the publication of Deleuze: A Philosophy of the Event to his untimely death in 2006, Fran's Zourabichvili was regarded as one of the most important new voices of contemporary philosophy in France. His work continues to make an essential contribution to Deleuze scholarship today, and this new translation is set to become an event within Deleuze Studies for many years to come'--Publisher's website.
Translations from the French of: Deleuze, une philosophie de l'{u296E}ement, Paris : PUF, 1994, and: Le vocabulaire de Deleuze, Paris : Ellipses, 2003.
Includes bibliographical references and index.
In English; translated from French.
Keywords: Deleuze, Gilles, -- 1925-1995 -- Criticism and interpretation; Deleuze, Gilles, -- 1925-1995 -- Language; Philosophy, French -- 20th century